2014
DOI: 10.1039/c4cc05339g
|View full text |Cite
|
Sign up to set email alerts
|

One-pot synthesized DNA-templated Ag/Pt bimetallic nanoclusters as peroxidase mimics for colorimetric detection of thrombin

Abstract: We developed a facile one-step approach to synthesize DNA-templated Ag/Pt bimetallic nanoclusters (DNA-Ag/Pt NCs), which possess highly-efficient peroxidase-like catalytic activity. With this finding, an aptamer based sandwich-type strategy is employed to design a label-free colorimetric aptasensor for the protein detection with high sensitivity and selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(46 citation statements)
references
References 40 publications
1
45
0
Order By: Relevance
“…The intrinsic fluorescence of metal NCs, which has been discussed in Section , can be readily used as an optical signal to sense the interactions of metal NCs with the biological species of interests. A variety of configurations exist to use the optical properties of metal NCs, ranging from colorimetric change, direct observation of fluorescence color change by naked eyes upon UV illumination, fluorescence enhancement (‘turn‐on’ assays) or fluorescence attenuation (‘turn‐off’ assays) . In this section, we will discuss the sensing mechanisms in different configurations, with a focus on identifying the prevailing recognition elements for biological sensing.…”
Section: Desirable Features Of Metal Ncs For Theranostic Applicationsmentioning
confidence: 99%
“…The intrinsic fluorescence of metal NCs, which has been discussed in Section , can be readily used as an optical signal to sense the interactions of metal NCs with the biological species of interests. A variety of configurations exist to use the optical properties of metal NCs, ranging from colorimetric change, direct observation of fluorescence color change by naked eyes upon UV illumination, fluorescence enhancement (‘turn‐on’ assays) or fluorescence attenuation (‘turn‐off’ assays) . In this section, we will discuss the sensing mechanisms in different configurations, with a focus on identifying the prevailing recognition elements for biological sensing.…”
Section: Desirable Features Of Metal Ncs For Theranostic Applicationsmentioning
confidence: 99%
“…TEM image showed that the size of the DNA−Au/Pt NCs was about 2 to 4 nm (Figure ), which was in agreement with previous report by Zheng 2014. The difference in size was probably due to the different lengths of oligonucleotide template . Also, the size distribution measured by DLS revealed that approximately over 60% of particles are between 5 to 7 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Su et al., with help of peroxidase property of Au@Pt nanoparticles designed a colorimetric biosensor for tracing Escherichia coli O157:H7 . Conjugation of peroxidase mimic nanostructure with bio‐receptor not only decreased catalytic activity but also diminish binding affinity of bio‐receptor . Nowadays DNA has been attractive for its potency as a scaffold for synthesis of nanoclusters .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enzyme-like nanomaterials (nanozymes) [1,2] based on metallic [3][4][5], metal oxide [6][7][8][9][10], bimetallic nanoparticles (NPs) and nanoclusters (NCs) [11][12][13][14], carbon nanomaterials [15][16][17], and hybrid nanocomposites [18][19][20][21][22][23][24][25], have recently received a great deal of attention for their biochemical applications. Enzyme-mimicking molecules (e.g., metal complexes, hemin and other porphyrins, cyclodextrins, and supramolecules) also have been reported to have many advantages over natural enzymes [26][27][28].…”
Section: Introductionmentioning
confidence: 99%